Our tree named Steve - Zweibel, Alan.; Catrow, David (New York : G.P. Putnam's Sons, 2005)
In a letter to his children, a father recounts memories of the role Steve, the tree in their front yard, has played in their lives.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Trees -- Fiction; Families -- Fiction; Letters -- Fiction; Trees -- Juvenile fiction; Families -- Juvenile fiction; Letters -- Juvenile fiction